2002
DOI: 10.5713/ajas.2002.812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Seasons on the Performance of Grey Giant Rabbits under Sub-Temperate Himalayan Conditions

Abstract: An experiment was conducted on 190 progeny (winter -74; summer -59; rainy -57) of 12 Grey Giant rabbits (10 female +2 males), to assess the effect of different seasons in a year, on their reproductive, growth and productive performances along with feed efficiency, under sub-temperate Himalayan conditions. The daily meteorological attributes recorded during winter (October to March), summer (April to June) and rainy (July to September) seasons, and analysed were minimum and maximum temperature, relative humidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 3 publications
11
11
0
Order By: Relevance
“…Prevalence of preweaning mortality due to insufficient milk supply and large litter size was the highest in winter (45.28%) while the lowest was in autumn (26.6%). Similar results were obtained by [31,32]. The prevalence of preweaning mortality because of cannibalism was 26.38%.…”
Section: Discussionsupporting
confidence: 84%
“…Prevalence of preweaning mortality due to insufficient milk supply and large litter size was the highest in winter (45.28%) while the lowest was in autumn (26.6%). Similar results were obtained by [31,32]. The prevalence of preweaning mortality because of cannibalism was 26.38%.…”
Section: Discussionsupporting
confidence: 84%
“…Other authors have observed no significant effect of season on LSB, LWB and LSW (BHATT et al 2002). BELHADI et al (2002) also support our findings that spring is the best season for reproduction of rabbits.…”
Section: Resultssupporting
confidence: 91%
“…In agreement with our results, Khalil and Mansour (1987) and El-Maghawry et al (1988) also noted higher values for litter size at weaning in spring, while Kumar et al (2005) reported a significant effect of season on gestation length in Angora rabbits. Similarly to our data, the absence of seasonal effects on fertility (Rodríguez and Fallas, 1999), litter size at birth and weaning (Bhatt et al, 2002) and sex ratio (Khalil and Mansour, 1987) has also been reported. In contrast, Ponce de Leon et al (2000) observed that the season had a significant effect on fertility, being higher in spring and lower in autumn.…”
Section: Resultssupporting
confidence: 56%
“…The increasing day length, comfortable temperature and availability of quality fodder during spring season may contribute to the high reproductive efficiency of rabbits in this period of the year. The pasture during spring was lush, having higher nutritive value with more protein and carotene content as compared to other seasons (Bhatt et al, 2002) and it has been observed that higher feed intake during lactation increased both litter size and weight at weaning (Pascual et al, 2002). Fertility, prolificacy, litter weight at birth, gestation length, and sex ratio were higher in rabbit does over 2 yr of age, followed by females of less than 1 yr of age and 1-2 yr old.…”
Section: Resultsmentioning
confidence: 99%